Shopping for Health: Yogurt - Stephanie B. Meyer; Ada Medina-Solórzano; Wendy J. Dahl (EDIS)
Yogurt has become a popular item in the American diet and has taken over the majority of the dairy section in many stores. Have you ever wondered what yogurt is, what its health benefits are, or what the differences are among the types of yogurts? Read this 4-page fact sheet to find the answers to these questions and to learn more about yogurt. Written by Stephanie B. Meyer, Ada Medina-Solórzano, and Wendy J. Dahl, and published by the UF Department of Food Science and Human Nutrition, January 2012.